Kazakh ornament as an element of national consciousness of the Kazakh people, the meaning and symbolism of ornament in Kazakh culture - Kalmenova Zhanna; Baizhanova Zhazira; Umralieva Bela; Tuyakbayeva Аigul; Myztafina Zhanna (Modern Scientific Technology, 2025)
This article examines a specific type of Kazakh fine art that symbolically reflects the inner world of a person and what surrounds him. These are patterns of rhythmically ordered elements that are harmonious in design, composition, and color. Kazakh national patterns have been known since the 16th century, and by the end of the 19th century they had taken a dominant place in the aesthetic culture of the people.